Reflections on the Qur'an: understanding surahs al-Fatihah & al-Baqarah. By Irfan Ahmad Khan. Leicestershire: The Islamic Foundation, 2005/1426 AH., pp. 782+xiii. ISBN 0 86037 455 6. - Khan, Israr Ahmad (IIUM Press, 2006)
Though the Holy Qur≥Én was first translated into English in 1649 by Alexander Ross, it remains a close text to most of the English readers, Muslims and non-Muslims alike. The book under review marks a departure from earlier efforts. It would definitely assist a person who, coming to this scripture for the first time, sincerely desires to penetrate its meaning to see how it influences the ordinary believer and his or her life, and how it penetrates the deepest layers of a Muslim conscience. ....